Examining the Relation Between Practicing Meditation and Having Peak Experiences and Lucid Dreams. A Cross-Sectional Study - Garcia-Campayo, Javier; Hijar-Aguinaga, Rinchen; Barceló-Soler, Alberto; Fernández-Martínez, Selene; Aristegui, Roberto; Pérez-Aranda, Adrián (Frontiers in Psychology, 2022)
The aim of this study was to compare meditators and nonmeditators in terms of their tendency to have peak experiences and their dream lucidity, while examining the associations between these outcomes and some related variables such as nondual awareness, mindfulness facets and absorption. In this cross-sectional study, 237 participants from general Spanish population completed an online survey that included ad hoc questions related to the study aim, along with the Five Facet Mindfulness Questionnaire (FFMQ), the Nondual Embodiment Thematic Inventory (NETI), the Tellegen Absorption Scale (TAS) and the Lucidity and Consciousness in Dreams Scale (LUCID). Of the total, 110 participants were identified as meditators and 127 as nonmeditators. More than half of the sample (58.2%) reported having experienced at least one peak experience in their life; these showed no differences in the number, intensity, or self-inducing ability of these experiences between both groups but were significantly more common among meditators (71.8% vs. 46.8%; p<.001), who also presented higher scores in most of the questionnaires, except for some LUCID subscales. Regression models demonstrated that being a meditator was a significant predictor of having had a peak experience, but not of LUCID scores. These results, which need to be interpreted considering the study limitations, support the potential of meditation to facilitate having peak experiences, while its impact on lucid dreams remains unclear.